Implementation of Improving Diversification and Community Food Security Program through Optimizing Yard Utilization in Tomohon City - Sambul, Hygia Jeanette; Kairupan, Sisca B.; Tarore, Steven (Technium Social Sciences Journal, 2025)
his study aims to determine, analyze and describe the implementation of the program to increase community food diversification and security through optimizing yard utilization in Tomohon City. Food diversification itself is an effort to increase the availability and consumption of food that is diverse, nutritionally balanced and based on the potential of local resources. This research uses a qualitative method with a research focus on increasing diversification and community food security through optimizing yard utilization in Tomohon City with sub-focus or indicators: socialization, resources, communication between agencies, social and economic conditions. The results showed that of the four indicators studied, various problems were found, namely: 1) Indicators of program socialization: limited clarity of socialization information, gaps between the program and the local needs of the community, and limited accessibility and infrastructure that hamper the smooth implementation of the program; 2) resource indicators: Limited capacity of Human Resources involved in the program, both in terms of knowledge and skills, limited budget, minimal use of technology, inadequate infrastructure and lack of participation and synergy between stakeholders; 3) inter-agency communication indicators: mismatches in information systems between agencies, differences in priorities and perspectives between agencies, lack of budget transparency, lack of community and private sector participation; 4) indicators of social and economic conditions: limited community income, low education levels which have an impact on low community understanding of the importance of food diversification, lack of community participation in program planning and implementation and lack of support from political elites so that the program has not been running effectively.